Citizen deliberation in the context of Uruguay's first National Water Plan - Marila Lázaro (IWA Publishing, 2021)
As part of the formulation of the first National Water Plan (NWP) in Uruguay, a mini-public process called ‘Citizen Deliberation on Water (Deci Agua)’ was developed in 2016. While the draft of the plan was being discussed in the formal arenas of water governance (Basin Commissions and Regional Water Resources Councils), a University research team (led by the authors), in coordination with the national water authority, adapted the mechanism of consensus conferences in order to incorporate the citizens’ visions and to contribute to public understanding of the NWP challenges. This article analyses the main aspects of the developed participation strategy and discusses them regarding a set of quality criteria used to evaluate deliberative processes. Although the final version of the NWP (passed by decree in 2017) incorporated some of the contributions of the Citizen Panel, an in-depth analysis of the scope of the deliberative process of Deci Agua allows us to delve into some key aspects related to the quality of participation processes and the challenges. A mixed approach that combines stakeholder participation and lay citizens is novel and desirable in water governance since it increases the scope of participation, deepens the legitimacy of decision-making and improves the public debate. Highlights Deci Agua was a citizen deliberation process based on consensus conferences.; A Citizen Panel contributed to the formulation of Uruguay's first National Water Plan.; The inclusion of the ethical dimension of water management was the main contribution.; Mini-publics like Deci Agua collaborate with the public debate.; Processes of citizen participation can complement stakeholder participation forums.;